Cytokinins in Dictyostelia – A Unique Model for Studying the Functions of Signaling Agents From Species to Kingdoms - Aoki, Megan M.; Emery, R. J. Neil; Anjard, Christophe; Brunetti, Craig R.; Huber, Robert J. (Frontiers in Cell and Developmental Biology, 2020)
Cytokinins (CKs) are a diverse group of evolutionarily significant growth-regulating molecules. While the CK biosynthesis and signal transduction pathways are the most well-understood in plant systems, these molecules have been identified in all kingdoms of life. This review follows the recent discovery of an expanded CK profile in the social amoeba, Dictyostelium discoideum. A comprehensive review on the present knowledge of CK biosynthesis, signal transduction, and CK-small molecule interactions within members of Dictyostelia will be summarized. In doing so, the utility of social amoebae will be highlighted as a model system for studying the evolution of these hormone-like signaling agents, which will set the stage for future research in this area.